Reconstructing Draft Genomes Using Genome Resolved Metagenomics Reveal Arsenic Metabolizing Genes and Secondary Metabolites in Fresh Water Lake in Eastern India. Issue 15 (June 2021) - Ghosh, Samrat; Sarangi, Aditya Narayan; Mukherjee, Mayuri; Singh, Deeksha; Madhavi, Madduluri; Tripathy, Sucheta
Rabindra Sarovar lake is an artificial freshwater lake in the arsenic infested eastern region of India. In this study, using the genome resolved metagenomics approach; we have deciphered the taxonomic diversity as well as the functional insights of the gene pools specific to this region. Initially, a total of 113 Metagenome Assembled Genomes (MAGs) were recovered from the two predominant seasons, that is, rainy (n = 50) and winter (n = 63). After bin refinement and de-replication, 27 MAGs (18 from Winter season and 9 from Rainy season) were reconstructed. These MAGs were either of high-quality (n = 10) or of medium quality (n = 17) that was determined based on genome completeness and contamination. These 27 MAGs spanning across 6 bacterial phyla and the most predominant ones were Proteobacteria, Bacteroidetes, and Cyanobacteria regardless of the season. Functional annotation across the MAGs suggested the existence of all known types of arsenic resistance and metabolism genes. Besides, important secondary metabolites such as zoocin_A, prochlorosin, and microcin were also abundantly present in these genomes. The metagenomic study of this lake provides the first insights into the microbiome composition and functional classification of the gene pools in two predominant seasons. The presence of arsenic metabolism and resistance genes in the recovered genomes is a sign of adaptation of the microbes to the arsenic contamination in this region. The presence of secondary metabolite genes in the lake microbiome has several implications including the potential use of these for the pharmaceutical industry.